Data visualization of family income and expenses / Aimi Amisha Ahmad Sabri and Mohd Nizam Osman - Ahmad Sabri, Aimi Amisha; Osman, Mohd Nizam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Data Visualization of Family Income and Expenses is proposed to help people to manage their income and expenses. Users will be able to plan and budget their finances using the data provided by the dashboard, as it will show average expenses compared to their income, the number of members, marital status, and many more. In this application, there is also data visualization applied to visualize what type of item they have spent on.